(untitled) (MSW Management Journal, 2026)
The Information Technology (IT) sector is characterised by rapid technological changes, tight deadlines, and high work demands, which can affect employees’ emotional wellbeing and engagement. This study investigates the impact of organisational culture on emotional wellbeing and employee engagement among IT professionals. The research aims to assess employees’ emotional wellbeing in relation to organisational culture, analyse engagement levels across different cultural settings, and explore the relationship between emotional wellbeing and engagement. A quantitative research design was adopted, with data collected from IT employees using a structured questionnaire. The findings reveal that organizational culture has a significant positive influence on both emotional wellbeing and employee engagement, and that employees with higher emotional wellbeing demonstrate greater engagement and commitment at work. The study highlights the importance of fostering a supportive and positive organisational culture, implementing wellbeing initiatives, and promoting employee-centered practices to enhance satisfaction, motivation, and retention in IT organizations.